Determining the Cognitive Profile of Patients with Multiple Sclerosis Based on the CANTAB Test - Nezhadi, Javad; Moradi , Alireza; Sadeghi, Meysam; Azadvari , Mohaddeseh; Abadi, Fatemeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The objective of this study was to determine the cognitive profile of patients with multiple sclerosis (MS) using the Cambridge Neuropsychological Test Automated Battery (CANTAB). Methods and Materials: This descriptive-analytical study was conducted on 94 patients with MS recruited from Ibn Sina Hospital in Tehran, selected through convenience sampling. Inclusion criteria comprised a neurologist-confirmed MS diagnosis, age between 20 and 50, disease duration of at least five years, and an EDSS score of ≤5. All participants had normal intelligence scores based on the Raven-2 Progressive Matrices (IQ 90–110). After completing the Motor Screening Task (MOT) to ensure physical and technical capability, participants were assessed using CANTAB subtests including Reaction Time (RTI), Rapid Visual Processing (RVP), Paired-Associate Learning (PAL), Spatial Working Memory (SWM), and Emotion Recognition Task (ERT). Statistical analysis involved one-sample t-tests with bootstrapping (5,000 samples) and a 95% confidence level. Results from the healthy population were extracted from a prior normative study. Findings: Statistically significant differences were found between MS patients and healthy individuals in all cognitive domains assessed except within and double errors in spatial working memory and the recognition of sadness, happiness, and surprise. MS patients exhibited higher motor screening error and latency scores (p = .007, p = .001), greater deficits in rapid visual processing (p < .001), prolonged reaction and movement times in both simple and choice tasks (p < .001), and poorer performance on paired-associate learning measures including total errors and trials (p < .001). Spatial working memory impairments were significant across several dimensions (p ≤ .005), and emotion recognition was significantly reduced for fear, anger, disgust, and overall accuracy (p ≤ .002). Conclusion: The CANTAB test effectively distinguishes cognitive deficits in MS patients across multiple domains and can be used as a reliable neuropsychological tool for early detection and targeted cognitive rehabilitation planning in clinical settings.